Single-Walled-Carbon-Nanotube-Modified Pyrolytic Graphite Electrode Used as a Simple Sensor for the Determination of Salbutamol in Urine - Rajendra N. Goyal; Sunita Bishnoi; Bharati Agrawal (International Journal of Electrochemistry)
A fast and sensitive voltammetric method has been proposed for the determination of salbutamol at single-walled-carbon-nanotube-modified edge-plane pyrolytic graphite electrode (SWNT/EPPGE) in human urine. The electrochemical response of salbutamol was determined by square wave voltammetry (SWV) in phosphate buffer solution (PBS) at physiological pH 7.2. The modified electrode showed improved voltammetric response towards the oxidation of salbutamol, and a well-defined anodic peak was observed at ~600 mV with enhanced peak current in comparison to the bare electrode. Linear calibration plot using SWNT/EPPGE was obtained in the concentration range of 50 to 2500 ngml-1 with sensitivity and detection limit of 2.15 nA/ngml-1 and 4.31 ngml-1, respectively. The developed method has been successfully applied for the determination of salbutamol in commercial preparations and human body fluids. Fast analysis of salbutamol in human urine makes the proposed method of great interest for doping control purposes at the site of competitive games.